Development and feasibility of an ambulatory acquisition system for fiber‐optic high‐resolution colonic manometry. Issue 12 (13th August 2019) - Wells, Cameron I.; Paskaranandavadivel, Nira; Lin, Anthony Y.; Du, Peng; Penfold, James A.; Dinning, Phil; Cheng, Leo K.; Bissett, Ian P.; Arkwright, John W.; O'Grady, Greg
Abstract: Background: High‐resolution colonic manometry is an emerging technique that has provided new insights into the pathophysiology of functional colorectal diseases. Prior studies have been limited by bulky, non‐ambulatory acquisition systems, which have prevented mobilization during prolonged recordings. Methods: A novel ambulatory acquisition system for fiber‐optic high‐resolution colonic manometry was developed. Benchtop validation against a standard non‐ambulatory system was performed using standardized calibration metrics. Clinical feasibility studies were conducted in three patients undergoing right hemicolectomy. Results: Pressure profiles obtained from benchtop testing were near‐identical using the ambulatory and the non‐ambulatory systems. Clinical studies successfully demonstrated ambulatory data capture with patients freely mobilizing postoperatively during continuous recordings of >60 hours. The occurrence ( P  = .56), amplitude ( P  = .65), velocity ( P  = .10), and extent ( P  = .12) of colonic motor patterns were similar to those obtained in non‐ambulatory studies. Conclusions: A novel ambulatory system for high‐resolution colonic manometry has been developed and validated. This technique will facilitate prolonged ambulatory recordings of colonic motor activity, assisting with investigations into the role of colonic motility in disease states. Abstract : A novel ambulatory system for high‐resolution colonic manometry has been developed and validated in benchtop and clinical studies. This technique will facilitate prolonged ambulatory recordings of colonic motor activity, assisting with future investigations into the role of colonic motility in disease states.